Autophagy inducer rapamycin treatment reduces IFN-I–mediated Inflammation and improves anti–HIV-1 T cell response in vivo - Wenli Mu; Valerie Rezek; Heather Martin; Mayra A. Carrillo; Shallu Tomer; Philip Hamid; Miguel A. Lizarraga; Tristan D. Tibbe; Otto O. Yang; Beth D. Jamieson; Scott G. Kitchen; Anjie Zhen (JCI Insight, 2022)
A hallmark of HIV-1 infection is chronic inflammation, even in patients treated with antiretroviral therapy (ART). Chronic inflammation drives HIV-1 pathogenesis, leading to loss of CD4+ T cells and exhaustion of antiviral immunity. Therefore, strategies to safely reduce systematic inflammation are needed to halt disease progression and restore defective immune responses. Autophagy is a cellular mechanism for disposal of damaged organelles and elimination of intracellular pathogens. Autophagy is pivotal for energy homeostasis and plays critical roles in regulating immunity. However, how it regulates inflammation and antiviral T cell responses during HIV infection is unclear. Here, we demonstrate that autophagy is directly linked to IFN-I signaling, which is a key driver of immune activation and T cell exhaustion during chronic HIV infection. Impairment of autophagy leads to spontaneous IFN-I signaling, and autophagy induction reduces IFN-I signaling in monocytic cells. Importantly, in HIV-1–infected humanized mice, autophagy inducer rapamycin treatment significantly reduced persistent IFN-I–mediated inflammation and improved antiviral T cell responses. Cotreatment of rapamycin with ART led to significantly reduced viral rebound after ART withdrawal. Taken together, our data suggest that therapeutically targeting autophagy is a promising approach to treat persistent inflammation and improve immune control of HIV replication.